Phagotrophic Protist Diversity in the Groundwater of a Karstified Aquifer – Morphological and Molecular Analysis. (27th June 2013) - Risse‐Buhl, Ute; Herrmann, Martina; Lange, Patricia; Akob, Denise M.; Pizani, Natalia; Schönborn, Wilfried; Totsche, Kai Uwe; Küsel, Kirsten
Abstract: To clarify the structure of microbial food webs in groundwater, knowledge about the protist diversity and feeding strategies is essential. We applied cultivation‐dependent approaches and molecular methods for further understanding of protist diversity in groundwater. Groundwater was sampled from a karstified aquifer located in the Thuringian Basin (Thuringia, Germany). Cultivable protist abundance estimated up to 8, 000 cells/L. Eleven flagellates, 10 naked amoebae, and one ciliate morpho‐species were detected in groundwater enrichment cultures. Most of the flagellates morpho‐species, typically < 10 μm, were sessile or free swimming suspension feeders, e.g., Spumella spp., Monosiga spp., and mobile, surface‐associated forms that grasp biofilms, e.g., Bodo spp. Naked amoebae, typically < 35 μm, that grasp biofilms were represented by, e.g., Vahlkampfia spp., Vannella spp., and Hartmanella spp. The largest fraction of the 18S rRNA gene sequences was affiliated with Spumella ‐like Stramenopiles. Besides, also sequences affiliated with fungi and metazoan grazers were detected in clone libraries of the groundwater. We hypothesize that small sized protist species take refuge in the structured surface of the fractures and fissures of the karstified aquifer and mainly feed on biofilm‐associated or suspended bacteria.